Surface Passivation of Layered MoSe2 via van der Waals Stacking of Amorphous Hydrocarbon - Lee, Do Hyeon; Dongquoc, Viet; Hong, Seongin; Kim, Seung Il; Kim, Eunjeong; Cho, Su yeon; Oh, Chang Hwan; Je, Yeonjin; Kwon, Mi Ji; Hoang Vo, Anh; Seo, Dong Bum; Lee, Jae Hyun; et al. (Small, 2022)
Development of efficient surface passivation methods for semiconductor devices is crucial to counter the degradation in their electrical performance owing to scattering or trapping of carriers in the channels induced by molecular adsorption from the ambient environment. However, conventional dielectric deposition involves the formation of additional interfacial defects associated with broken covalent bonds, resulting in accidental electrostatic doping or enhanced hysteretic behavior. In this study, centimeter-scaled van der Waals passivation of transition metal dichalcogenides (TMDCs) is demonstrated by stacking hydrocarbon (HC) dielectrics onto MoSe2 field-effect transistors (FETs), thereby enhancing the electric performance and stability of the device, accompanied with the suppression of chemical disorder at the HC/TMDCs interface. The stacking of HC onto MoSe2 FETs enhances the carrier mobility of MoSe2 FET by over 50% at the n-branch, and a significant decrease in hysteresis, owing to the screening of molecular adsorption. The electron mobility and hysteresis of the HC/MoSe2 FETs are verified to be nearly intact compared to those of the fabricated HC/MoSe2 FETs after exposure to ambient environment for 3 months. Consequently, the proposed design can act as a model for developing advanced nanoelectronics applications based on layered materials for mass production.
Keywords: Ambient environment; Amorphous hydrocarbons; Dichalcogenides; Field-effect transistor; Molecular adsorption; Stackings; Surface passivation; Transition metal dichalcogenides; Van der Waal; Van der waal stacking; field-effect transistors; hydrocarbons; surface passivation; transition metal dichalcogenides; van der Waals stacking